2021
DOI: 10.2217/imt-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors Use and Effects on Prognosis of COVID-19 Infection: A Systematic Review and Meta-Analysis

Abstract: Aim: We aimed to quantify the effects of immune checkpoint inhibitors (ICIs) on the prognosis of COVID-19. Materials & methods: A meta-analysis was conducted and the hospitalization, severe disease and mortality rates were assessed. Thirteen studies comprising of 4614 cancer patients with COVID-19 were included. Results: When compared with cancer patients without prior ICI exposure, patients with prior ICI treatment exhibited a higher rate of hospitalization (odds ratio [OR] 2.0, 95% CI 1.19–3.38, p = 0.01… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
(104 reference statements)
0
9
0
Order By: Relevance
“…While eight other published systematic reviews have examined IT in this patient group, the present one has notable strengths: it is the most recent study; it included three to four times the number of reports in the final analysis of mortality and severe events; it examined two times the number of published studies with adjusted outcome data and almost five times the number of studies with ICI patients alone (Supplementary‐Table 5). 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 Unfortunately, GRADE analysis demonstrated that even with this increasing body of data the certainty of evidence regarding the effects of ICIs in cancer patients with COVID‐19 is very low.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While eight other published systematic reviews have examined IT in this patient group, the present one has notable strengths: it is the most recent study; it included three to four times the number of reports in the final analysis of mortality and severe events; it examined two times the number of published studies with adjusted outcome data and almost five times the number of studies with ICI patients alone (Supplementary‐Table 5). 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 Unfortunately, GRADE analysis demonstrated that even with this increasing body of data the certainty of evidence regarding the effects of ICIs in cancer patients with COVID‐19 is very low.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 , 18 , 19 While an ideal study examining the impact of ICIs on COVID‐19 outcomes would adjust for these variables and a systematic review addressing this question would focus on such adjusted studies, this has generally not been the case. 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 Among eight published systematic reviews of studies investigating cancer patients presenting with COVID‐19 that previously received immunotherapies (IT) including ICIs, only 3 provided analyses of adjusted outcomes with IT, and each of these was based on five or fewer published studies. 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 Furthermore, only two of these systematic reviews specifically differentiated between ICIs and non‐ICI ITs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations